Three basic principles of designing programs of teaching English to adults who learn it outside university language programs - Тарнопольський, Олег Борисович (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2016)
The paper discusses the founding principles for teaching English to adults in outside-university language courses. The principles include: developing courses on the basis of learners’ needs; taking into account their attitudes to teaching methods; and every course’s autonomy, structural, informational, organizational, and objective completeness combined with the structural, informational, organizational, and objective ties uniting all the courses. The suggested principles regulate the organization of teaching/learning, formulating its goals, selecting contents, and choosing its methods.